1993
DOI: 10.1002/mpo.2950210705
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the choroid plexus: A pediatric experience

Abstract: Carcinoma of the choroid plexus (CCP) is a rare tumor of the central nervous system which occurs more frequently in patients under 3 years of age. We report 10 cases of CCP in children. There were 5 males and 5 females, aged 5 to 84 months at diagnosis (median 32 months). Eight CCP were located in the lateral ventricle and 2 in the fourth ventricle. All patients underwent initial surgery, with complete resection in 5 cases. Postoperative treatment included radiotherapy alone in 4 patients, chemotherapy alone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
1
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 33 publications
1
25
1
9
Order By: Relevance
“…Only one patient remain alive 5 years after initial treatment. These results support the poor prognosis and high mortality rate of CPC.KEY WORDS: brain neoplasm, choroid plexus tumours, choroid plexus carcinoma, immunohistochemistry.Os tumores do plexo coróide são neoplasias raras do sistema nervoso central (SNC), originados do epitélio de revestimento dos plexos coróides localizado nos ventrículos cerebrais e que correspondem a 0,4 a 0,6% de todos os tumores cerebrais [1][2][3][4][5][6] . Em sua maioria são tumores benignos,…”
unclassified
“…Only one patient remain alive 5 years after initial treatment. These results support the poor prognosis and high mortality rate of CPC.KEY WORDS: brain neoplasm, choroid plexus tumours, choroid plexus carcinoma, immunohistochemistry.Os tumores do plexo coróide são neoplasias raras do sistema nervoso central (SNC), originados do epitélio de revestimento dos plexos coróides localizado nos ventrículos cerebrais e que correspondem a 0,4 a 0,6% de todos os tumores cerebrais [1][2][3][4][5][6] . Em sua maioria são tumores benignos,…”
unclassified
“…Radiation therapy alone was not suggested for CPCs in the pediatric patient population due to the intolerable and undesirable side effects [1,15,17]. Several articles support the use of post-operative treatments such as combined therapies or adjuvant chemotherapy alone [12,15,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that combined therapy versus chemotherapy alone yielded increased survival [13]. However, radiation therapy alone was found not to contribute to survival [17]. Due to this tumor's tendency to disseminate throughout the cerebral spinal fluid space, it is believed that treatment of the entire neuraxis is necessary [14].…”
Section: Discussionmentioning
confidence: 99%
“…Alguns dados de neuroimagem podem ser sugestivos de malignidade: grande volume tumoral, invasão do parênquima encefálico, edema, hidrocefalia e por vezes herniação ou desvio de linha média 6 . A ressonância nuclear magnética (RM), permite melhor visualização da extensão, limites do tumor e suas relações anatômicas, facilitando desta forma o tratamento cirúrgico e o controle de lesões residuais no pós-operatório 5 .…”
Section: Discussionunclassified
“…A quimioterapia apresenta-se como instrumento valioso a ser associado ao tratamento cirúrgico, sendo válida associação de várias drogas para tumores parcialmente ressecáveis ou para controle da doença residual no pós-operatório. Não existe, entretanto, consenso acerca do quimioterápico de escolha, devido à dificuldade na elaboração de protocolos tendo em vista a raridade do tumor 6 . O comportamento biológico agressivo do tumor justifica, portanto, o seu prognóstico reservado, com taxas de sobrevida média em torno de 9 meses em crianças e 3,5 anos em adultos 14 .…”
Section: Discussionunclassified